IMPLEMENTASI HUKUM WARIS ISLAM PADA MASYARAKAT KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Purbenazir, Eka Rahayu (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
This study raises the issue of implementation inheritance practices in society Kepahiang District of Kepahiang. So the urgency to fix the system of inheritance which has become a tradition for generations was considered good by most people Kepahiang to return it to the Islamic inheritance in order to create a qualified Muslim community. The purpose of this study (1) To investigate the implementation of the community Kepahiang inheritance; (2) To identify the background on which to base  the distribution of the next of kin; (3) To analyze  the views of Islamic law on inheritance practices implementation in society  Kepahiang and  add  related intellectual treasures of Islamic  heritage. This study uses  content analysis  (content analysis),  with a historical-normative approach. The results  showed that (1) In general  practice division of the estate made by the people Kepahiang is with individual bilateral  inheritance system  through  the deliberation and peace, this is done  to anticipate disputes among  heirs and to the achievement of welfare. It is also a habit of going on and practiced repeatedly and well-regarded in the community, while the comparison section received between heirs male and female heirs depending on the results  of consultation with emphasis on the principle  of mutual  benefit  and willingly accept any portion  thereof,  more often equally or 1:1; (2) The basis for the implementation of the division of inheritance in Kepahiang society is based on its own  traditions  that have been embraced for generations. Although there  are based on the Islamic inheritance, only when executing by way of inheritance Islam, then the disagreement / dispute they choose to implement with the tradition that has been handed down it; (3) The distribution of inheritance in the District Kepahiang society Kepahiang using a system of equal division is not in accordance with Islamic  law, because the  procedure of distribution carried out by dividing the  average whole  inheritance to the  heir on the  legal basis  is very weak.  But the  practice of the  division of the  estate in the  District Kepahiang society can be viewed  as the result of social construction, but in this Islamic regards  the division of inheritance practices such as ‘urf fasid because it is contrary to the text (Nash) of syariat. Especially if the grounds  of gender equality that will bring destruction and not in line with the objectives of the estabilishment of syari’at.